The effects of respiratory muscle training on respiratory function and functional capacity in patients with early stroke: a meta-analysis - Yun-Shan Zhang; Kai Zhang; Lang Huang; Jing-Xue Wei; Zi-Ting Bi; Jing-Hua Xiao; Jian Huang; Chao-Song Luo; Ying-Dong Li; Jia-Mei Zhang (European Review of Aging and Physical Activity, 2024)
Abstract Background Respiratory muscle training is a continuous and standardized training of respiratory muscles, but the evidence of the effects on early stroke patients is not clear. This meta-analysis aimed to investigate the effects of respiratory muscle training on respiratory function and functional capacity in patients with early stroke. Methods PubMed, Embase, PEDro, ScienceDirect, AMED, CINAHL, and China National Knowledge Infrastructure databases were searched from inception to December 8, 2023 for articles about studies that 1) stroke patients with age ≥ 18 years old. Early stroke < 3 months at the time of diagnosis, 2) respiratory muscle training, including inspiratory and expiratory muscle training, 3) the following measurements are the outcomes: respiratory muscle strength, respiratory muscle endurance, pulmonary function testing, dyspnea fatigue score, and functional capacity, 4) randomized controlled trials. Studies that met the inclusion criteria were extracted data and appraised the methodological quality and risk of bias using the Physiotherapy Evidence Database scale and the Cochrane Risk of Bias tool by two independent reviewers. RevMan 5.4 with a random effect model was used for data synthesis and analysis. Mean differences (MD) or standard mean differences (SMD), and 95% confidence interval were calculated (95%CI). Results Nine studies met inclusion criteria, recruiting 526 participants (mean age 61.6 years). Respiratory muscle training produced a statistically significant effect on improving maximal inspiratory pressure (MD = 10.93, 95%CI: 8.51–13.36), maximal expiratory pressure (MD = 9.01, 95%CI: 5.34–12.69), forced vital capacity (MD = 0.82, 95%CI: 0.54–1.10), peak expiratory flow (MD = 1.28, 95%CI: 0.94–1.63), forced expiratory volume in 1 s (MD = 1.36, 95%CI: 1.13–1.59), functional capacity (SMD = 0.51, 95%CI: 0.05–0.98) in patients with early stroke. Subgroup analysis showed that inspiratory muscle training combined with expiratory muscle training was beneficial to the recovery of maximal inspiratory pressure (MD = 9.78, 95%CI: 5.96–13.60), maximal expiratory pressure (MD = 11.62, 95%CI: 3.80–19.43), forced vital capacity (MD = 0.87, 95%CI: 0.47–1.27), peak expiratory flow (MD = 1.51, 95%CI: 1.22–1.80), forced expiratory volume in 1 s (MD = 0.76, 95%CI: 0.41–1.11), functional capacity (SMD = 0.61, 95%CI: 0.08–1.13), while inspiratory muscle training could improve maximal inspiratory pressure (MD = 11.60, 95%CI: 8.15–15.05), maximal expiratory pressure (MD = 7.06, 95%CI: 3.50–10.62), forced vital capacity (MD = 0.71, 95%CI: 0.21–1.21), peak expiratory flow (MD = 0.84, 95%CI: 0.37–1.31), forced expiratory volume in 1 s (MD = 0.40, 95%CI: 0.08–0.72). Conclusions This study provides good-quality evidence that respiratory muscle training is effective in improving respiratory muscle strength, pulmonary function, and functional capacity for patients with early stroke. Inspiratory muscle training combined with expiratory muscle training seems to promote functional recovery in patients with early stroke more than inspiratory muscle training alone. Trial registration Prospero registration number: CRD42021291918.